Analys av skärkrafter och brottytans utseende vid bearbetning av trä - Jankeel, Firas (2016)
On behalf of Luleå University I have preformed tests in a cutting force machine for studying the bottom surface and its appearance and at the same time measure cutting forces. The contract also includes taking pictures in the electron microscope to study the fracture surfaces of the cut material and the chips. The tests have been performed with different angles of cutting tools, different cutting directions and different depths of cut on pine material. The cutting edge sharpness and edge geometry is also studied in the microscope. The aim of the thesis is to study the strength and surface characteristics in the processing of wood. The work should help Luleå University by providing expertise in the design of cutting tools such as saw blades and chain saws. The result is a study of nine rounds where the fracture surfaces, cutting forces and microscope images are studied and reported. Validerat; 20160622 (global_studentproject_submitter)